The Implementation of Permenpan-RB No 29/2011 in Crisis Management of Government Public Relations - Rachmat Kriyantono (Universitas Muhammadiyah Yogyakarta, 2019)
This study aims to evaluate whether Public Relations practitioners have implemented the principles of the Regulation of the Minister of Administrative Reform and Bureaucratic Reform (Permenpan-RB) No. 29 of 2011 concerning The Guidelines for Crisis Management within government agencies. A crisis is an unexpected event that threatens public expectations, has the potential to produce negative things, affects the performance and reputation of an institution. In the era of democracy, the threat of a greater crisis occurs because the public has a critical character, is free to give opinions, and is free to access information from various channels, including the internet. Crisis must be managed well because a crisis is possible for every institution and it has a negative or positive impact on the institution. PR is communication management and crisis develops due to communication factors so that PR is a crisis manager. By conducting in-depth interviews with 23 government public relations practitioners, this study found that Permenpan-RB No. 29 of 2011 had not been fully applied. This study confirms that the structural position of public relations plays an important role in public relations activities. This research reinforces the literature review on crises that government public relations practitioners tend to devise ways to prevent crises after the cause of the crisis is known and public relations practitioners are not yet proactive in crisis prevention planning. This research contributes to the study and practice of government public relations as a socialization that public relations rules in Indonesia have adopted the ideal principle of public relations based on academic literature.